Analisis Faktor Kepercayaan, Manfaat Dan Keamanan Terhadap Minat Penggunaan E-Money Dalam Perspektif Ekonomi Syariah (Studi Kasus Pada Masyarakat di Boyolali) - Sumadi Sumadi; Abdul Haris Romdhoni; Fatakhurohim Fatakhurohim (Jurnal Ilmiah Ekonomi Islam, 2022)
Information and communication technology is currently developing rapidly, one of which is the payment system. In the past, payments were made using cash, but now they are starting to apply non-cash payments. E-money is a means of payment in electronic form in which the money or balance will be stored on a chip or server. The study aims to determine the influence of trust, benefit, and security factors on the interest in using E-money in Boyolali. The method used in this research is Multiple Linear Regression. The research method used is a quantitative study using a questionnaire as a collection material. The number of research respondents was determined to be 100 respondents. Sampling technique used in this study is purposive sampling. The test results of this study indicate that trust variable has a positive and significant effect on the interest in using E-money in Boyolali, with a probability value of 0.000. Benefits variable do not have a significant effect on the interest in using E-money in Boyolali, with a probability value of 0.471. Security variable have a positive and significant effect on the interest in using E-money in Boyolali, with a probability value of 0.013.